2013
DOI: 10.1177/1098612x13514420
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of alfaxalone to induce and maintain anaesthesia in cats undergoing neutering procedures

Abstract: This study looked at the use and efficacy of alfaxalone for total intravenous anaesthesia (TIVA) in cats. Following intramuscular medetomidine (20 μg/kg) and morphine (0.3 mg/kg) premedication, anaesthesia was induced and maintained with intravenous alfaxalone. Patients were breathing 100% oxygen. Heart rate (HR), respiratory rate (RR), end-tidal carbon dioxide, oxygen saturation of haemoglobin and indirect arterial blood pressure via Doppler (DAP) were recorded every 5 mins. Thirty-four cats (10 males and 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In the present study, apnoea was not observed in any case. It has been described that post-induction apnoea is an uncommon finding when alfaxalone is administered IV to young and adult cats (Zaki et al 2009;O'Hagan et al 2012;Beths et al 2014). Similarly to our study, apnoea has not been reported after IM administration of alfaxalone in combination with dexmedetomidine in cats (Grubb et al 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, apnoea was not observed in any case. It has been described that post-induction apnoea is an uncommon finding when alfaxalone is administered IV to young and adult cats (Zaki et al 2009;O'Hagan et al 2012;Beths et al 2014). Similarly to our study, apnoea has not been reported after IM administration of alfaxalone in combination with dexmedetomidine in cats (Grubb et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…; Beths et al. ). Similarly to our study, apnoea has not been reported after IM administration of alfaxalone in combination with dexmedetomidine in cats (Grubb et al.…”
Section: Discussionmentioning
confidence: 97%
“…Dose-dependent decrease in systolic arterial pressure and systemic vascular resistance, due to a vasodilatory effect, have previously been reported after clinical and supraclinical induction doses of alfaxalone in dogs and cats (Muir et al, 2008;Muir et al,, 2009). Furthermore, alfaxalone administered in either boluses or CRI for TIVA may cause hypotension in cats (Beths et al, 2014;Schwarz et al, 2014). However, either no side effects or minimal changes in the hemodynamic parameters have been shown after alfaxalone CRI in dogs (Ambros et al, 2008) and horses (Goodwin et al, 2018).…”
Section: Figure 2 Graphical Representation (From Top Left To Bottom mentioning
confidence: 99%
“…; Beths et al. ), but no direct comparison of the two drugs can be found in the literature. The main difference between these agents seems to be the effect on respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Alfaxalone and propofol have both been used for induction and maintenance of anaesthesia in cats (Andress et al 1995;Liehmann et al 2006;Muir et al 2009;Beths et al 2014), but no direct comparison of the two drugs can be found in the literature. The main difference between these agents seems to be the effect on respiration.…”
Section: Introductionmentioning
confidence: 99%